2017
DOI: 10.1016/j.scitotenv.2016.08.205
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae biofilm in soil: Greenhouse gas emissions, ammonia volatilization and plant growth

Abstract: Microalgal biofilm in soils represents an alternative fertilization method for agricultural sustainability. In the present study, greenhouse gas emission, soil ammonia volatilization, and the growth of Pennisetum glaucum were evaluated under the effect of a microalgal biofilm, commercial urea, and a control (without application of a nitrogen source). CH emissions were equal for the three treatments (p>0.05). CO emissions significantly increased in microalgal biofilm treatment (p<0.01), which was also responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 26 publications
1
34
1
1
Order By: Relevance
“…Indeed biomass production of 153 g and 547 g were respectively noticed for the fertilization at the time of transplant and 22 days prior the time of transplant [25]. According to many authors [26,46,47], even growing plants with microalgae biomass wasn't better than those grown with synthetic fertilizers or digestate, the use of microalgal biomass for fertilizing purposes presents some important advantages. Microalgal biomass can be considered as a slow-released fertilizer since the application of dried biomass to soils would not result in emissions Table 4.…”
Section: Agronomic Trials By Plant Growth and Lixiviation Testsmentioning
confidence: 99%
“…Indeed biomass production of 153 g and 547 g were respectively noticed for the fertilization at the time of transplant and 22 days prior the time of transplant [25]. According to many authors [26,46,47], even growing plants with microalgae biomass wasn't better than those grown with synthetic fertilizers or digestate, the use of microalgal biomass for fertilizing purposes presents some important advantages. Microalgal biomass can be considered as a slow-released fertilizer since the application of dried biomass to soils would not result in emissions Table 4.…”
Section: Agronomic Trials By Plant Growth and Lixiviation Testsmentioning
confidence: 99%
“…The study also alluded to the necessity in understanding and using the interactions between mass and radiative transfer, physiology of the microorganisms, and their radiation and substrate kinetics and dynamics. In addition to these components, we have also identified that biofilm formation is important, whether it is a structure to be avoided or fostered as a design feature [66].…”
Section: Comparison Of Eulerian and Lagrangian Methodologiesmentioning
confidence: 99%
“…There is a net increment of biomass production yield compared to typical activated sludge processes. This could have an impact in energy recovery (through biogas) but also in sludge waste disposal expenses, which can be partially counteracted by downstream production of high value-added bioresources as proteins, prebiotics and probiotics[31] or bioplastics, as well as energetic resources as third generation liquid biofuels[66].…”
mentioning
confidence: 99%
“…Microalgae biomass application in soils is beneficial for crops and yields (Shaaban, 2001), the organic matter, carbon content and biological activity in soils increase with these microorganisms (Castro et al, 2017;Miralles et al, 2012;Xie et al, 2007). Microalgae, specifically when they are obtained from wastewater treatments (De-Bashan and Bashan, 2004), contains several nutrients removed from the treated sewage.…”
Section: Climate-smartmentioning
confidence: 99%
“…Considering that CSA is oriented to reduce GHG emissions and enhance the productivity of agricultural ecosystems, microalgae culture and production can be a decisive factor for future scenarios. Several experiments were conducted to study the benefits of microalgae in agriculture, from the fertility perspective (Mulbry et al, 2005;Raposo and Morais, 2011;Renuka et al, 2016;Shaaban, 2001) to the environmental approach (Castro et al, 2017;Egle et al, 2016;Renuka et al, 2016).…”
Section: Microalgae Culturementioning
confidence: 99%